2021
DOI: 10.3390/polym13081314
|View full text |Cite
|
Sign up to set email alerts
|

Starch-Based Super Water Absorbent: A Promising and Sustainable Way to Increase Survival Rate of Trees Planted in Arid Areas

Abstract: This research aimed to scale up the production of starch-based super water absorbent (SWA) and to validate the practical benefits of SWA for agricultural applications. SWA was successfully prepared in an up-scaling production by radiation-induced graft polymerization of acrylic acid onto cassava starch. Chemical characterization by FTIR and thermal characterization by TGA showed results that differentiated starting materials from the prepared SWA, thus confirming effective preparation of starch-based SWA via r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…e FTIR spectrum of bentonite showed telescopic vibration absorption peaks at 3449 cm −1 (-OH in the structure of bentonite), 1634 cm −1 (-OH in interlayer water), and 1034 cm −1 (-O-Si in bentonite) and bending vibration absorption peaks of -O-Si at 521 cm −1 and 465 cm −1 . Comparison of the absorption peaks of bentonite and the SAR revealed that the telescopic vibration and bending vibration absorption peaks of -O-Si still existed in the spectrum of the resin, but the absorption peak was weak, indicating that the vibration dipole moment had changed, and bentonite had graft polymerized with AA and bound to the polymer chain of the resin through chemical bonds [30]. us, these findings showed that the highly absorbent resin was a crosslinked polymer formed by the polymerization of potato starch, bentonite, and AA.…”
Section: Water Retentionmentioning
confidence: 99%
“…e FTIR spectrum of bentonite showed telescopic vibration absorption peaks at 3449 cm −1 (-OH in the structure of bentonite), 1634 cm −1 (-OH in interlayer water), and 1034 cm −1 (-O-Si in bentonite) and bending vibration absorption peaks of -O-Si at 521 cm −1 and 465 cm −1 . Comparison of the absorption peaks of bentonite and the SAR revealed that the telescopic vibration and bending vibration absorption peaks of -O-Si still existed in the spectrum of the resin, but the absorption peak was weak, indicating that the vibration dipole moment had changed, and bentonite had graft polymerized with AA and bound to the polymer chain of the resin through chemical bonds [30]. us, these findings showed that the highly absorbent resin was a crosslinked polymer formed by the polymerization of potato starch, bentonite, and AA.…”
Section: Water Retentionmentioning
confidence: 99%
“…Development of a method for synthesizing carbon nanodots by radiation processing. By relying on free radicals that are susceptible to a reaction when water breaks down through gamma rays [24][25][26][27]. This synthesis process is not only free from harsh chemicals and synthesized at room temperature, but also has the potential to produce on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Active reducing agents (H or e aq À ) and oxidizing agents (HO , H 2 O 2 , O 2 ) can be produced at room temperature from gamma radiolysis. [28][29][30][31] Radiolysis could be an alternative strategy for modification of ACs structure avoiding the use of toxic reagents or solvents, thereby generating less waste. [28][29][30][31] This research aims to modify the structure of ACs derived from glutinous rice using gamma radiolysis (25 kGy) for LSB electrode applications, and probe the effects of media (distilled water and ammonia solution) used in the irradiation process on the physical, chemical, and electrical properties of the materials.…”
Section: Introductionmentioning
confidence: 99%